2010
DOI: 10.1177/1352458510371408
|View full text |Cite
|
Sign up to set email alerts
|

Remyelination of optic nerve lesions: spatial and temporal factors

Abstract: Optic neuritis provides an in vivo model to study demyelination. The effects of myelin loss and recovery can be measured by the latency of the multifocal visual evoked potentials. We investigated whether the extent of initial inflammatory demyelination in optic neuritis correlates with the remyelinating capacity of the optic nerve. Forty subjects with acute unilateral optic neuritis and good visual recovery underwent multifocal visual evoked potentials testing at 1, 3, 6 and 12 months. Average latency changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 72 publications
6
45
1
Order By: Relevance
“…20,21 VEP was also used in single or small multicentre clinical studies assessing high-dose intravenous immunoglobulin, erythropoietin, simvastatin, and phenytoin in patients with acute optic neuritis, [22][23][24][25] and in natural recovery observational studies after an acute optic neuritis episode. 12,16,17,[26][27][28] When baseline characteristics of participants enrolled in RENEW were compared with those in trials of other candidate remyelinating or neuroprotective drugs, age and percentage of women were similar, mean number of days from fi rst acute optic neuritis symptom to fi rst dose was 24 days in RENEW versus 5-20 days in previous acute optic neuritis studies. 7,[22][23][24][25] A study testing erythropoietin reported shorter VEP latencies at week 16 for erythropoietin than for placebo, but the reported VEP latency was already shorter at baseline, resulting in an absence of treatment eff ect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 VEP was also used in single or small multicentre clinical studies assessing high-dose intravenous immunoglobulin, erythropoietin, simvastatin, and phenytoin in patients with acute optic neuritis, [22][23][24][25] and in natural recovery observational studies after an acute optic neuritis episode. 12,16,17,[26][27][28] When baseline characteristics of participants enrolled in RENEW were compared with those in trials of other candidate remyelinating or neuroprotective drugs, age and percentage of women were similar, mean number of days from fi rst acute optic neuritis symptom to fi rst dose was 24 days in RENEW versus 5-20 days in previous acute optic neuritis studies. 7,[22][23][24][25] A study testing erythropoietin reported shorter VEP latencies at week 16 for erythropoietin than for placebo, but the reported VEP latency was already shorter at baseline, resulting in an absence of treatment eff ect.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation in the design of the RENEW study, we calculated the diff erence in aff ected eye VEP latency over time using the unaff ected fellow eye baseline value as the pretreatment normal reference value. 12,16 Although variable between individuals, 11 VEP usually has a very small inter-eye latency variation in the absence of disease pathology and is highly reproducible for sequential testing under standardised testing conditions. 12,16,17 To ensure that the baseline of the fellow eye was normal, participants with a diagnosis of multiple sclerosis or ophthalmological disorders were excluded and the fellow eye had to have a normal VEP at screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine sufficient amplitude, software automatically calculate signal to noise ratio (SNR) at each segment of the stimulated visual field. The signal was considered non-recordable in segments where amplitude of the response was less than 1.96 times of the noise level (determined as Standard Deviation of the trace within the interval 400-1000 ms) (Klistorner et al, 2010).…”
Section: Mfvep Recording and Analysismentioning
confidence: 99%
“…While some spontaneous remyelination occurs, most patients have residual structural and clinical deficits 1, 2, 3, 4. A physiological hallmark of AON is prolonged visual evoked potential (VEP) latency, resulting from persistent demyelination of the affected optic nerve 2, 5…”
Section: Introductionmentioning
confidence: 99%